Harnessing Social Media Marketing to Boost Customer Engagement in Islamic Financial Services - Febrianto, Achmad; Maulida, Leny (Journal of Educational Management Research, 2025)
In the ever-evolving digital era, social media marketing strategies have become a key element for financial institutions, including those based on Islamic principles. This study focuses on how a Sharia-compliant institution implements social media marketing strategies to increase customer awareness, interest, and decision-making in choosing its financial products. This study uses a qualitative descriptive approach, with data collection techniques through direct interviews with field appraisers and digital promotion staff. The research also highlights the importance of utilizing social media as a means of accelerating access to information and strengthening relationships between institutions and customers. The findings indicate that social media marketing has a significant influence on customer decisions in selecting Islamic financial services. Of the total 262 customers in 2025, approximately 60% stated that they were attracted to the product due to promotions conducted through social media by the institution’s staff and agents. The study also uncovers various factors that support and hinder the effectiveness of digital marketing and emphasizes the importance of transparency and security of product information, which were previously little known to the public. Implications for educational management include the need for curriculum development that integrates digital marketing literacy and Islamic economic principles, especially in vocational and higher education institutions.